A Comprehensive Review of the Pathophysiology and Clinical Importance of Iliac Vein Obstruction. (July 2020) - Esposito, Antonino; Charisis, Nektarios; Kantarovsky, Alexander; Uhl, Jean F.; Labropoulos, Nicos
Abstract : Objective: The purpose of this comprehensive review is to give a historical account of iliac vein compression and to analyse the pathophysiological aspects and their clinical implications. Methods: An extensive search of the databases was performed from inception until 2019. The patterns, length and site of compression, wall and luminal changes, and anatomical variations were some of the factors recorded and analysed. Results: Twenty-seven studies were included in this review, divided into cadaveric, histological, and imaging. According to the literature 22%–32% of the asymptomatic population shows "spurs" at the origin of the left common iliac vein (LCIV). Imaging studies also show the presence of direct and indirect compression signs such as the presence of collateral venous flow in axial, transpelvic, or ascending lumbar collaterals, and >50% compression in 37%–44% of the asymptomatic population. In patients without thrombosis it is unknown what produces the signs and symptoms, as the obstruction pre-exists their development. Haemodynamic evaluation is found in only a few studies often including patients with previous deep vein thrombosis. Furthermore, most of the tests are performed with the patient in the supine position and therefore the haemodynamic information is relatively poor. Conclusion: Patients with venous obstruction have various clinical presentations from being asymptomatic to having venous claudication and skin damage. Obstruction should be placed into clinical context, together with other contributing factors. Proper evaluation and clinical judgement are important in selecting patients for treatment. Given that such selection is not always clear, further work is needed.